2019
DOI: 10.1002/pon.5107
|View full text |Cite
|
Sign up to set email alerts
|

Exploring emotion regulation as a mediator of the relationship between resilience and distress in cancer

Abstract: Objectives Distress in patients with cancer is a significant problem that affects up to 32% of patients. Yet research indicates that 35% of cancer patients do maintain high levels of well‐being. Resilience is one psychological factor implicated as being protective against distress; however, the mechanisms for this relationship are currently unknown. The present study aimed to explore emotion regulation as a potential mediator of the relationship between resilience and distress. Methods A cross‐sectional survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 35 publications
4
26
0
Order By: Relevance
“…These results indicate the need for training programs like emotion regulation for schizophrenia patients' caregivers. Vaughan et al [31] examined 277 patients with cancer and showed that the effect of resilience on distress was fully mediated by emotion regulation, which is consistent with the results of this study. Steinhardt and Dolbier [32] showed that individual resilience could be enhanced by training, which might have a positive effect on significant clinical outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…These results indicate the need for training programs like emotion regulation for schizophrenia patients' caregivers. Vaughan et al [31] examined 277 patients with cancer and showed that the effect of resilience on distress was fully mediated by emotion regulation, which is consistent with the results of this study. Steinhardt and Dolbier [32] showed that individual resilience could be enhanced by training, which might have a positive effect on significant clinical outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…High emotion regulation capacity, biologically reflected by prefrontal inhibition, is considered as a key mechanism in psychological health, hence crucial for adaptive functioning (Aldao et al, 2010;Gross, 2007). Our findings support pre-pandemic data suggesting that emotion regulation serves as mediator of the relationship between resilience and distress (Vaughan et al, 2019), and expand latest findings suggesting that individual differences in emotion regulation prospectively predict early COVID-19 related acute stress (Tyra, Griffin, Fergus, & Ginty, 2021). Specifically, we suggest that interventions aimed at emotion regulation might be especially warranted as a modality to enhance resilience (Lee et al, 2020;Renna, Fresco, & Mennin, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…In this way, patients who present lower resilience show greater problems in relation to emotional regulation and, as a consequence, higher levels of stress and anxiety. Such findings were stated by Vaughan et al [ 29 ]…”
Section: Introductionsupporting
confidence: 76%